Исследования напряжения срабатывания высоковольтных газонаполненных неуправляемых разрядников электроразрядных погружных установок - Жекул, Василий Григорьевич; Мельхер, Юрий Иванович; Поклонов, Сергей Георгиевич; Смирнов, Алексей Петрович; Швец, Иван Сафронович (НТУ "ХПИ", 2016)
В работе выполнено экспериментальное исследование влияния параметров технологических режимов работы электроразрядной погружной установки (изменение частоты следования разрядов от 0,2 до 2 Гц, температуры окружающей среды от 10 °С до 90 °С, количества разрядов) на величину напряжения срабатывания его высоковольтного газонаполненного неуправляемого разрядника. Показано, что влияние указанных параметров может быть существенным и требующим введения циклических режимов работы электроразрядной погружной установки для повышения эффективности обработки скважин.

The experimental investigation of the influence of parameters of technological modes of operation of the electrodischarge immersion installation intended to increase production rate of oil wells (the change of the repetition frequency of discharges of 0.2 to 2 Hz, ambient temperature from 10 °C to 90 °C, the number of discharges) by the value of the operation voltage of its high voltage gasfilled spark gap uncontrollable discharger is accomplished in the study. It is established that the increase of temperature leads to the increase of the operation voltage, and increasing the repetition rate and quantity of discharges lead to the decreasing response voltage of the discharger. In this case the obtained dependency can reveal regions of saturation. It is shown that the influence of these parameters may be significant and requires the introduction of cyclic modes of operation of the electrodischarge immersion installation for improved efficiency in the processing of wells.
Study of voltage operation of the high-voltage gas-filled noncontrollable dischargers of the electrodischarge immersion installation
Keywords: высоковольтный разрядник; температура окружающей среды; частота следования разрядов; ЭПУ; ambient temperature